Towards mixed physical node reservoir computing: light-emitting synaptic reservoir system with dual photoelectric output - Lian, Minrui; Gao, Changsong; Lin, Zhenyuan; Shan, Liuting; Chen, Cong; Zou, Yi; Cheng, Enping; Liu, Changfei; Guo, Tailiang; Chen, Wei; Chen, Huipeng (Light, science & applications, 2024)
Memristor-based physical reservoir computing holds significant potential for efficiently processing complex spatiotemporal data, which is crucial for advancing artificial intelligence. However, owing to the single physical node mapping characteristic of traditional memristor reservoir computing, it inevitably induces high repeatability of eigenvalues to a certain extent and significantly limits the efficiency and performance of memristor-based reservoir computing for complex tasks. Hence, this work firstly reports an artificial light-emitting synaptic (LES) device with dual photoelectric output for reservoir computing, and a reservoir system with mixed physical nodes is proposed. The system effectively transforms the input signal into two eigenvalue outputs using a mixed physical node reservoir comprising distinct physical quantities, namely optical output with nonlinear optical effects and electrical output with memory characteristics. Unlike previously reported memristor-based reservoir systems, which pursue rich reservoir states in one physical dimension, our mixed physical node reservoir system can obtain reservoir states in two physical dimensions with one input without increasing the number and types of devices. The recognition rate of the artificial light-emitting synaptic reservoir system can achieve 97.22% in MNIST recognition. Furthermore, the recognition task of multichannel images can be realized through the nonlinear mapping of the photoelectric dual reservoir, resulting in a recognition accuracy of 99.25%. The mixed physical node reservoir computing proposed in this work is promising for implementing the development of photoelectric mixed neural networks and material-algorithm collaborative design. This manuscript proposes a photoelectric dual-output mixed physical node reservoir system. It achieves higher handwriting digit recognition accuracy and use the photoelectric output characteristics to achieve multichannel image recognition.